2022
DOI: 10.1039/d2nj01057g
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature synthesis of Ag3PO4 nanoparticles with the assistance of trisodium citrate for photocatalytic dye degradation

Abstract: The cubic silver phosphate (Ag3PO4) nanoparticles (NPs) are prepared with the assistance of trisodium citrate. By control the reaction time, different size of Ag3PO4 was obtained. The possible growth mechanism...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The SEM micrograph of the composite catalyst TS82/AgP16 in Figure 2 c shows that the Ag 3 PO 4 nanoparticles are uniformly distributed on the surface of TS82 microspheres and titania silica microspheres are decorated with Ag 3 PO 4 nanoparticles with an average size of 40 nm (inset of Figure 2 d). It is also noteworthy to observe that in case of pristine Ag 3 PO 4 , aggregated particles of 200 to 300 nm were formed due to rapid nucleation in the reaction solution leading to crystal growth [ 43 ]. However, this feature is absent in the composite material indicating that the TS82 microspheres act as nucleation controlling medium leading to nearly uniform distribution of the small sized (~50 nm) Ag 3 PO 4 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM micrograph of the composite catalyst TS82/AgP16 in Figure 2 c shows that the Ag 3 PO 4 nanoparticles are uniformly distributed on the surface of TS82 microspheres and titania silica microspheres are decorated with Ag 3 PO 4 nanoparticles with an average size of 40 nm (inset of Figure 2 d). It is also noteworthy to observe that in case of pristine Ag 3 PO 4 , aggregated particles of 200 to 300 nm were formed due to rapid nucleation in the reaction solution leading to crystal growth [ 43 ]. However, this feature is absent in the composite material indicating that the TS82 microspheres act as nucleation controlling medium leading to nearly uniform distribution of the small sized (~50 nm) Ag 3 PO 4 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…6 In many narrow-bandgap semiconductors, silver phosphate (Ag 3 PO 4 ) has a highly dispersed conduction band and good electrostatic induction, which can accelerate the separation of photo-generated carriers, thus exhibiting unparalleled high quantum efficiency. [7][8][9] In recent years, researchers have demonstrated that Ag 3 PO 4 exposed with different active facets has significantly different photocatalytic properties. 10 Among them, Ag 3 PO 4 tetrapods exposed to high-reactive {110} facets have better photocatalytic performance due to its double coordination of multiple suspended bonds, which can provide more active sites.…”
Section: Introductionmentioning
confidence: 99%
“…At present, water pollution treatment methods include biological treatment, 6 physical adsorption, 7,8 chemical oxidation, 9 and photocatalytic degradation. 10,11 Among them, photocatalysis stands out among many methods due to its advantages of low cost, high degradation rate, environmental friendliness, and no formation of secondary pollutants. 12…”
Section: Introductionmentioning
confidence: 99%
“…At present, water pollution treatment methods include biological treatment, 6 physical adsorption, 7,8 chemical oxidation, 9 and photocatalytic degradation. 10,11 Among them, photocatalysis stands out among many methods due to its advantages of low cost, high degradation rate, environmental friendliness, and no formation of secondary pollutants. 12 The photocatalytic reaction is a reaction system formed by the oxidation and reduction of photogenerated electrons and holes on the surface of the catalyst, which requires the photocatalytic materials to have an appropriate electronic band structure and good stability.…”
Section: Introductionmentioning
confidence: 99%